Subcutaneous immunotherapy in a patient taking ofatumumab for multiple sclerosis and upadacitinib for atopic dermatitis - Twan Sia, BA; Leeon Bacchus, BA; Stanley Liu, BS; John Leung, MD (Journal of Allergy and Clinical Immunology: Global)
Allergen-specific immunotherapy has not been well-studied in the setting of increasingly common immune system-targeting medications. Subcutaneous immunotherapy may not be contraindicated in patients taking anti-CD20 mAbs antibodies and/or Janus kinase inhibitors.